The Australian Mainstream Media’s Portrayal of Youth Climate Activism and Dissent - Cowan, Jacob Micah; Dzidic, Peta; Newnham, Elizabeth (Qualitative Sociology Review, 2023)
The March 2019 School Strikes 4 Climate, predominantly organized by young students, garnered widespread and polarizing media coverage. We aimed to identify how Australian mainstream print news media portrays youth involvement and dissent within climate action movements. A qualitative media framing analysis was conducted to determine how youth climate activists and dissent were presented during the first large-scale youth climate protests in Australia. Australian newspaper articles and opinion pieces (N = 101) were identified via ProQuest and screened. An inductive thematic analysis was conducted in NVivo12. Findings were assessed through a typology of dissent to determine how different forms of dissent were represented in the Australian print news media. The framing of dissent in Australian media coverage was varied, with news articles being more likely to prioritize the voices of young people, while opinion pieces resorted to fear-mongering rhetoric that critiqued and invalidated their agency. Protestors used combinations of dutiful and disruptive dissent to advocate for climate action, with the latter being more effective for challenging systemic drivers of climate change.